Quantitative ¹³C-urea breath test values predict peptic ulcer risk in Helicobacter pylori -infected children: a retrospective study - Pan, Xiaoting; Chen, Youtao; Li, Haibo; Ye, Hong (Frontiers in Pediatrics, 2025)
BackgroundThe quantitative ¹³C-urea breath test (¹³C-UBT) is valuable for diagnosing Helicobacter pylori (H. pylori) infection. However, pediatric-specific thresholds and their association with peptic ulcer (PU) disease remain inadequately defined. This study aimed to identify optimal pediatric delta over baseline (DOB) thresholds for diagnosing H. pylori infection and explore associations with ulcer risk in children.MethodsIn this retrospective study, 1,034 consecutive children aged 3–18 years undergoing ¹³C-UBT with endoscopy and histopathological evaluation at Fujian Children's Hospital (May 2021–May 2025) were enrolled. DOB cutoff values were determined by ROC analysis. Logistic regression and restricted cubic spline (RCS) analyses evaluated associations between DOBs and ulcer risk.ResultsThe optimal pediatric-specific cutoff was 5.285% [Sensitivity 84%, Specificity 90%, area under the curve (AUC) 0.879]. Children with ulcers had significantly higher median DOBs than those without (3.1% vs. 1.9%; P < 0.001). A clear dose–response trend was observed across DOB quartiles (P < 0.001). Ulcer risk increased with DOB up to approximately 36.39‰, beyond which the risk plateaued.ConclusionsA DOB cutoff of 5.285‰ provides excellent diagnostic accuracy for pediatric H. pylori infection. Higher DOBs correlate strongly with increased bacterial load, mucosal inflammation, and peptic ulcer (PU) risk up to ∼36.39‰, indicating a saturation effect. Quantitative DOB thus offers diagnostic and prognostic utility, supporting its integration into regional pediatric guidelines.